2020
DOI: 10.1088/1361-6668/abb789
|View full text |Cite
|
Sign up to set email alerts
|

A new concept for developing a compact joint structure for reducing joint resistance between high-temperature superconductors (HTS) and low-temperature superconductors (LTS)

Abstract: It is significantly difficult to develop a superconducting joint between REBCO and low-temperature superconductors (LTS) using a solder matrix replacement technique. This is because the REBCO superconducting layer is highly corrosive to Sn. In this work, TEM observations were first conducted on the reaction interface between the REBCO layer and Sn to reveal the reaction. Then, a new idea to create a compact low-resistance joint to reduce the joint resistance between REBCO and LTS was proposed. In this method, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In order to form a superconducting joint, superconducting solders via the sheath-dissolution method were employed. It was found, however, that Sn in the solder solution deteriorates the superconductor's surface, making joint resistance orders of 10 −10 Ω [55], however this is acceptable for the persistent-mode operation of the 1.3 GHz NMR magnet.…”
Section: Superconducting Joints and Persistent-mode Operationmentioning
confidence: 99%
“…In order to form a superconducting joint, superconducting solders via the sheath-dissolution method were employed. It was found, however, that Sn in the solder solution deteriorates the superconductor's surface, making joint resistance orders of 10 −10 Ω [55], however this is acceptable for the persistent-mode operation of the 1.3 GHz NMR magnet.…”
Section: Superconducting Joints and Persistent-mode Operationmentioning
confidence: 99%
“…This can be attributed to the chemical difficulty in forming superconducting joints between ceramic HTS and metallic superconducting solders. Banno et al [48] recently reported the challenges faced when developing superconducting joints for REBCO using a solder owing to the highly corrosive nature of the REBCO superconducting layer under Sn in the solder.…”
Section: Overview Of the Superconducting Joint Technology For Hts Con...mentioning
confidence: 99%
“…HTS conductors by soldering. The REBCO thin film of a CC is corrosive under exposure to Sn in the solder, it is difficult to achieve a superconducting joint between a REBCO CC and the solder including Sn [48]. In contrast, Mousavi et al [109] attempted to form the superconducting joint between reacted Bi-2212/Ag wires through soldering.…”
Section: Attempts and Difficulties Of Superconducting Joint Formentioning
confidence: 99%
See 2 more Smart Citations